Study Of Jadid Literature In Foreign Literary Studies - Kenjayev Farkhod Ikram ugli (International Journal Of Literature And Languages, 2025)
This article analyzes the study of Jadid literature in foreign literary studies, particularly in the research of Jeff Sahadeo. The study scientifically illuminates Sahadeon's views on the colonial policy of the Russian Empire in Turkestan, local society, and the Jadid movement. Also, the reflection of the educational and political activities of the Jadids in foreign sources, the role of Jadidism in the process of national self-awareness and modernization are assessed on the basis of an analytical approach.